2004
DOI: 10.1111/j.0736-8046.2004.21107.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Sarcoid‐like Granulomas in a Patient with X‐Linked Hyper‐IgM Syndrome

Abstract: We describe a 5-year-old boy with red-pink, firm, nodular lesions, with central resolution and prominent borders, localized to the face, backs of the hands, extensor surfaces of the arms and legs, and the buttocks. He also had recurrent bacterial respiratory infections. Quantitative immunoglobulin levels revealed hypogammaglobulinemia and increased IgM levels. Histopathologic examination of a nodular lesion revealed perivascular and periadnexal granulomas composed of epithelioid cells surrounded by a mantle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…It has been reported that T-cell deficiencies or imbalanced production of cytokines in CVID patients with granulomatosis may lead to abnormal sequestration of antigen and subsequent formation of granulomas [25]. Similar immune dysfunctions observed in some HIGM patients may enhance susceptibility to generate granulomatous lesions [3]. As previously reported for different locations of granulomatosis [2,26,27] IV Ig replacement therapy did not provide any therapeutic effect.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been reported that T-cell deficiencies or imbalanced production of cytokines in CVID patients with granulomatosis may lead to abnormal sequestration of antigen and subsequent formation of granulomas [25]. Similar immune dysfunctions observed in some HIGM patients may enhance susceptibility to generate granulomatous lesions [3]. As previously reported for different locations of granulomatosis [2,26,27] IV Ig replacement therapy did not provide any therapeutic effect.…”
Section: Discussionmentioning
confidence: 68%
“…All these syndromes are characterized by recurrent bacterial infections. However, susceptibility to autoimmune disorders and granulomatous diseases frequently observed in CVID [1,2] and HIGM [3][4][5] may be related to T-cell defects.…”
Section: Introductionmentioning
confidence: 99%
“…Included were all primary publications published in English, German and French. Ten primary reports were found describing cutaneous granulomas in A-T [4,5,6,7,8,9,10,11,12,13] and a series of articles reporting skin granulomas in other PIDs [14,15,16,17,18,19,20,21,22,23,24,25,26]. For common variable immunodeficiency (CVID), often associated with granulomas in various organs, only the recently published article of Ardeniz and Cunningham-Rundles [23] dealing with skin granulomas was included.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies on skin granulomas were cancelled: 2 studies describing lesions in a patient with X-linked hyper-IgM [24] and IgA deficiency [25], because from the decription the lesions appeared sarcoid-like not resembling the skin granulomas in A-T, and 1 study on a man with X-linked agammaglobulinaemia [26] because the paper was published in 1991 before the btk gene analysis became available and the description of the patient did not fit to what is now known for X-linked agammaglobulinaemia.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Whether malignant transformation follows chronic infection or inflammation of the hepatobiliary tree is unknown [14]. Other than hepatobiliary neoplasms, there have been reports linking XHIGM syndrome with oat cell carcinoma of the colon [18], cutaneous sarcoid like granulomas [19], and Kaposi sarcoma [20]. To the best of our knowledge, this is the first reported case of poorly differentiated neuroendocrine tumor seen in association with XHIGM.…”
Section: Discussionmentioning
confidence: 96%